Moral torch fishing: A signaling theory of blame. (24th October 2019) - Shoemaker, David; Vargas, Manuel
Abstract: It is notable that all of the leading theories of blame have to employ ungainly fixes to deflect one or more apparent counterexamples. What these theories share is a content‐based theory of blame's nature. Such approaches overlook or ignore blame's core unifying feature, namely, its function, which is to signal the blamer's commitment to a set of norms. In this paper, we present the problems with the extant theories and then explain what signaling is, how it functions in blame, why appealing to it resolves the problems in other theories, what the signaling function implies for a wider range of gray‐area cases, and what the larger significance is of blame's core function for interpersonal interactions in a variety of (non‐moral) normative domains.